The Alkanes with Maximum Wiener Polarity Index. Issue 1 (9th August 2018) - Du, Zhibin; Ali, Akbar
Abstract: The Wiener polarity index (usually denoted by W p ) of an alkane is the number of unordered pairs of carbon atoms which are separated by three carbon–carbon bonds. This topological index W p is useful for predicting the boiling points of alkanes. Deng [MATCH Commun. Math. Comput. Chem. 66 (2011) 305] proved that the maximum W p value among all alkanes, with n carbon atoms, is 3 n - 15 . The main purpose of present paper is to find all those alkanes with n carbon atoms, which attain the maximum value of W p . Abstract :